Model of Organization of Distance Learning for Students of Architectural Specialties - E. A. Dyachkova (Открытое образование (Москва), 2022)
The article is devoted to the organization of distance education for students of architectural specialties of universities. Designing a distance-learning model, which consists in the scientific substantiation of the structure and content of the distance-learning model for preparing students of architectural specialties. The article also presents an analysis of scientific literature, the purpose of which is to generalize knowledge in the field of distance learning and professional training in relation to architectural education. A historiographic analysis of the problem was carried out, the categorical apparatus of the study and the terminological base were specified, criteria and indexes of the formation of students’ preparation - architects for professional activities in the process of distance learning were identified.The problem lies in the scientific substantiation of the structure and content of the distance-learning model for students of architectural specialties of universities.The purpose of this paper is to develop and scientifically and pedagogically justify a distance-learning model for preparing students of architectural specialties.Research methods. To test the initial provisions and achieve the goals set at different stages of the study, the following theoretical methods were used: analysis of regulatory documents and psychological and pedagogical literature, historical and pedagogical analysis.The main part of the article reveals a distance-learning model for preparing students of architectural specialties. The distance-learning model includes the following blocks: target, which includes the goal of organizing distance learning to train students of architectural specialties; methodological, including system-activity, personality-oriented, axiological, competence-based approaches and their corresponding principles; meaningful, including readiness components: (motivational, cognitive, activity-practical, creative, evaluative-reflective), as well as pedagogical conditions: creating positive motivation for learning, the presence of educational communication, improving the student’s readiness to use distance learning technologies, providing stages training: information-theoretical, practice-oriented, integration; organizational and procedural, including organizational forms of distance learning for the preparation of students of architectural specialties of universities: synchronous, asynchronous; distance learning methods; means; learning technologies; diagnostic, including criteria and indexes: motivational, cognitive, activity-practical, creative, evaluative-reflective, as well as levels: receptive, receptive-reproductive, reproductive-productive, productive, creative; effective - including the results of the organization of distance learning for the preparation of students of architectural specialties.Conclusion. The concept of training students of architectural specialties of universities has been clarified. Preparation of students - architects for professional activities in the process of distance learning is a pedagogical process aimed at organizing the work of students - architects, contributing to the development of motivational, cognitive, activity-practical, creative, evaluative-reflexive components. A model of distance learning for students of architectural specialties has been developed, characterized by consistency, stability and integrativity of its constituent components: target; methodological; substantive, organizational and procedural, diagnostic and productive. The concept of distance learning model is disclosed. The ideas about distance learning have been expanded; the results and conclusions make a certain contribution to the theory of distance learning in terms of using the possibilities of distance learning to organize the educational process in an architectural university. The model of distance learning for students of architectural specialties is described.